Performance and role of the breast lesion excision system (BLES) in small clusters of suspicious microcalcifications. Issue 1 (January 2016) - Scaperrotta, Gianfranco; Ferranti, Claudio; Capalbo, Emanuela; Paolini, Biagio; Marchesini, Monica; Suman, Laura; Folini, Cristina; Mariani, Luigi; Panizza, Pietro
Abstract: Purpose: To assess the diagnostic performance of the BLES as a biopsy tool in patients with ≤1 cm clusters of BIRADS 4 microcalcifications, in order to possibly avoid surgical excision in selected patients. Materials: This is a retrospective study of 105 patients undergone to stereotactic breast biopsy with the BLES. It excises a single specimen containing the whole mammographic target, allowing better histological assessment due to preserved architecture. Results: Our case series consists of 41 carcinomas (39%) and 64 benign lesions (61%). Cancer involved the specimen margins in 20/41 cases (48.8%) or was close to them (≤1 mm) in 14 cases (34.1%); margins were disease-free in only 7 DCIS (17.1%). At subsequent excision of 39/41 malignant cases, underestimation occurred for 5/32 DCIS (15.6%), residual disease was found in 15/39 cancers (38.5%) and no cancer in 19/39 cases (48.7%). For DCIS cases, no residual disease occurred for 66.7% G1–G2 cases and for 35.3% G3 cases ( P = 0.1556) as well as in 83.3%, 40.0% and 43.8% cases respectively for negative, close and positive BLES margins ( P = 0.2576). Conclusions: The BLES is a good option for removal of small clusters of breast microcalcifications, giving better histological interpretation, lower underestimation rates and possibly reducing the need of subsequent surgical excision in selected patients.